Fundamentals of horizontal wellbore cleanout : theory and applications of rotary jetting technology /: theory and applications of rotary jetting technology. (2022) - Song, Xianzhi; Li, Gensheng; Shah, Subhash; Xu, Zhengming
No abstract available